Perceptions of the general public and physicians regarding open disclosure in Korea: a qualitative study. Issue 1 (December 2016) - Ock, Minsu; Kim, Hyun; Jo, Min-Woo; Lee, Sang-il
Abstract Background Experience with open disclosure and its study are restricted to certain western countries. In addition, there are concerns that open disclosure may be less suitable in non-western countries. The present study explored and compared the in-depth perceptions of the general public and physicians regarding open disclosure in Korea. Methods We applied the COREQ (Consolidated Criteria for Reporting Qualitative Research) checklist to this qualitative study. We conducted 20 in-depth interviews and four focus group discussions with 16 physicians and 18 members of the general public. In-depth interviews and focus group discussions were performed according to semi-structured guidelines developed according to a systematic review of open disclosure. We conducted a directed content analysis by analyzing the verbatim transcripts and field notes in accordance with the predetermined guidelines. Results Open disclosure perceptions were summarized in terms of the "five Ws and one H" (who, what, where, when, why, and how). All physician and general public participants acknowledged the normative justifiability of open disclosure. The participants mostly agreed on the known effects of open disclosure, but the physicians had negative opinions on its expected effects, such as decreased intention of the general public to file lawsuits and increased credibility of medical professionals. Generally, the participants thought that open disclosure is required for medical errors causing major harm. However, the physicians and general public had conflicting opinions on the need for open disclosure of near misses. Most physicians did not know how to conduct open disclosure and some physicians had bad experiences due to inappropriate or incomplete open disclosure. Conclusion Physicians and the general public in Korea acknowledge the need for open disclosure. Guidelines according to the type of patient safety incident are required to encourage physicians to more readily conduct open disclosure. Furthermore, hospitals need to consider organizing a dedicated team and hiring experts for open disclosure.